Licenciatura em música, ações afirmativas e diretrizes nacionais curriculares para a educação das relações étnico-raciais: o caso da UFSCAR e da UFRB - Melo, Luísa Maria Matos de (2024)
This study aimed to investigate how the Bachelor of Music Education programs at two different Brazilian federal universities from different regions have been adapting, within the curricular scope, to the demands raised by the National Curricular Guidelines for Ethnic-Racial Relations Education (DCNs ERER). The proposal was to analyze the curricula and syllabi of the mentioned courses regarding the integration of themes related to ethnic-racial relations, as well as to understand the perception of students and graduates regarding this integration. This research involved a qualitative exploratory perspective, utilizing documentary and bibliographical analysis, in addition to semi-structured interviews. From the analysis of the Course Pedagogical Projects of the Federal University of Recôncavo da Bahia (UFRB) and the Federal University of São Carlos (UFSCar), it is also possible to obtain a more comprehensive overview of the influence of the different contexts in which they are inserted in the design of the curricula in question. Juxtaposing the data gleaned from the curricular analysis with the data procured from student interviews reveals a discrepancy between the propositions outlined in the documents and the students' perceptions of their implementation. Generally, the hypotheses suggest that curricula tend to incorporate the overarching principles of regulations, rather than the specific details, in most instances.